Implementasi Pendidikan Inklusif di Sekolah Dasar Kabupaten Merauke: Analisis Tantangan dan Solusinya - Pranyoto, Yohanes Hendro; Berangka, Dedimus (Jurnal Masalah Pastoral, 2025)
This study adopted a descriptive qualitative approach with a phenomenological paradigm to understand the practices, barriers, and strategies for developing an inclusive culture in 102 primary schools in the Merauke district selected through cluster sampling from a population of 209 schools. Data were collected through semi-structured interviews, online questionnaires, and documentation studies, then analyzed using a cycle of reduction, presentation, and conclusion drawing. Results show that 84% of schools have not implemented the inclusion paradigm thoroughly, with existing implementation limited to learning adjustments and individualized assessments. Six main barriers were identified: unsupportive school policies and leadership, teachers' competence and lack of role of Special Assistance Teachers, rigid education unit curriculum, limited infrastructure, lack of professional experts, and suboptimal local government and community support. As a solution, it is recommended to strengthen the policy and vision-mission of inclusive schools, develop the professionalism of inclusive teachers and socialize Special Assistance Teachers, modify a more adaptive curriculum, improve accessibility infrastructure and adaptive learning media, add experts and strategic partners, develop a comprehensive support system, and collaborate across sectors.